2015
DOI: 10.1021/acs.jpcb.5b09864
|View full text |Cite
|
Sign up to set email alerts
|

Aspheric Solute Ions Modulate Gold Nanoparticle Interactions in an Aqueous Solution: An Optimal Way To Reversibly Concentrate Functionalized Nanoparticles

Abstract: Nanometer-sized gold particles (AuNPs) are of peculiar interest because their behaviors in an aqueous solution are sensitive to changes in environmental factors including the size and shape of the solute ions. In order to determine these important characteristics, we performed all-atom molecular dynamics simulations on the icosahedral Au144 nanoparticles each coated with a homogeneous set of 60 thiolates (4-mercapto-benzoate, pMBA) in eight aqueous solutions having ions of varying sizes and shapes (Na+, K+, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Mass spectrometry has already become an important tool (along with microscopy, crystallography, spectroscopy, and centrifugation , ) for determination and characterization of novel MPC compositions. , Combined mass spectrometry and X-ray crystallographic analysis has confirmed the structures of the types of MPCs examined in the present report, detailing both the core architecture and protecting ligand composition. Au 25 (pMBA) 18 ( p MBA = para -mercaptobenzoic acid) is composed of a 13-atom icosahedral gold core surrounded by six protecting dimeric ligand “staples” each comprising three ligands and two gold atoms [−SR–​Au–​SR–​Au–​SR−]; Au 36 (pMBA) 24 is composed of a 28-atom face-centered cubic gold core enclosed by four dimeric staples and 12 simple bridging thiolates [−Au–​SR–​Au−] .…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Mass spectrometry has already become an important tool (along with microscopy, crystallography, spectroscopy, and centrifugation , ) for determination and characterization of novel MPC compositions. , Combined mass spectrometry and X-ray crystallographic analysis has confirmed the structures of the types of MPCs examined in the present report, detailing both the core architecture and protecting ligand composition. Au 25 (pMBA) 18 ( p MBA = para -mercaptobenzoic acid) is composed of a 13-atom icosahedral gold core surrounded by six protecting dimeric ligand “staples” each comprising three ligands and two gold atoms [−SR–​Au–​SR–​Au–​SR−]; Au 36 (pMBA) 24 is composed of a 28-atom face-centered cubic gold core enclosed by four dimeric staples and 12 simple bridging thiolates [−Au–​SR–​Au−] .…”
supporting
confidence: 70%
“…Deciphering the novel structures of MPC materials make them prime candidates for examination by mass spectrometry 11 and chromatography. 12−14 Mass spectrometry has already become an important tool (along with microscopy, crystallography, spectroscopy, and centrifugation 15,16 ) for determination and characterization of novel MPC compositions. 17,18 Combined mass spectrometry and X-ray crystallographic analysis has confirmed the structures of the types of MPCs examined in the present report, detailing both the core architecture and protecting ligand composition.…”
mentioning
confidence: 99%
“…The wide range of Au–pMBA clusters investigatedranging from aurous-thiolate oligomers (∼2–4 kDa) to classic smaller metallic clusters like (25,18), at ∼8-kDa, all the way to the classic larger (144,60) at ∼37-kDamay serve as model systems of comparatively high rigidity and (surface) charge density. The specific solution parameters required for effective ESI processes provide intriguing clues to the fundamental physicochemical solution-phase properties of these clusters. , Furthermore, our results offer some fascinating insights into this “classic” gold–pMBA series, e.g., the surprise (or delayed) appearance in apparent high abundance of the nonclassical (36,24) species.…”
Section: Introductionmentioning
confidence: 83%
“…Villareal et al found that sodium (Na + ) counterions, and by extension other small hydrophilic cations, create strong salt bridges linking aq-Au 144 (pMBA) 60 (pMBA = paramercaptobenzoic acid) clusters. 13 Subsequently, they predicted the strong ion pairing that results when these alkali ions are replaced by bulky quaternary ammonium cations, namely, tetramethylammonium (TMA+) counterions, 12 which thereby prevents the attractive salt-bridge interaction between clusters. However, TMA + is nonvolatile and thus ineligible for ESI-MS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[28] With regard to biomedical applications, a desirable property of gold nanoparticles is their ability to aggregate reversibly into nanoclusters of controlled size when placed in a special solution, and to dissociate back into individual nanoparticles when introduced into the body. [29, 30, 31, 32] Finally, we compare the binding affinity of Au 18 with those of Au 102 [33] and Au 144 [34, 35, 36, 37, 38, 39, 40, 32], functionalized by the same ligand under the same near-physiological conditions.…”
Section: Introductionmentioning
confidence: 99%